ON-LINE EDUCATION: DEVELOPING COMPETITIVE ADVANTAGE (Journal of Information Technologies in Education (ITE), 2007)
This article examines the evolution of on-line university programs in the United States and describes the key strategic challenges this new technology offers for existing universities. It suggests possible strategic plans for universities interested in gaining and sustaining a competitive advantage in the world of international distance learning.